Comparing BERT Against Traditional Machine Learning Models in Text Classification - Garrido-Merchan, Eduardo C.; Gozalo-Brizuela, Roberto; Gonzalez-Carvajal, Santiago (Journal of Computational and Cognitive Engineering, 2023)
The BERT model has arisen as a popular state-of-the-art model in recent years. It is able to cope with NLP tasks such as supervised text classification without human supervision. Its flexibility to cope with any corpus delivering great results has make this approach very popular in academia and industry. Although, other approaches have been used before successfully. We first present BERT and a review on classical NLP approaches. Then, we empirically test with a suite of different scenarios the behaviour of BERT against traditional TF-IDF vocabulary fed to machine learning models. The purpose of this work is adding empirical evidence to support the use of BERT as a default on NLP tasks. Experiments show the superiority of BERT and its independence of features of the NLP problem such as the language of the text adding empirical evidence to use BERT as a default technique in NLP problems.